The oversight of outsourcing US intelligence after 9/11: private intelligence contractors - Sungur, Bülent (New Security Challenges, 2025)
This book is a story about Private Intelligence Contractors (PICs) and their relationship with the United States executive and legislative principals in the War on Terror when the line between the public and private sectors has been increasingly blurred. PICs have challenged the traditional approach which assumes that sensitive intelligence tasks should be performed by government officials because of their importance for national security. So this book examines the principal-agent relationship and the oversight problem between PICs, the US Intelligence Community (IC), the president and Congress after the 9/11 attacks. The book demonstrates that by exploiting information asymmetry, adversely selected PICs can violate legislative rules and goals such as by performing inherently governmental tasks, colluding with the IC, capturing the control of the task and contractual process, abuse, waste and fraud. In addition, to get around congressional oversight and achieve his or her hidden agenda, the executive principal can also mismanage contractors through the IC or delegate contractors to perform inherently governmental tasks